Taxonomic reassessment of Parasesarma (Crustacea: Brachyura: Decapoda: Sesarmidae) based on genetic and morphological comparisons, with the description of a new genus. Issue 4 (25th April 2020) - Shahdadi, Adnan; Fratini, Sara; Schubart, Christoph D
Abstract: Parasesarma is a species-rich genus whose representatives are common in wetlands and mangroves of the Indo-Pacific. Morphologically, the genus is heterogeneous and has been postulated to constitute a polyphyletic taxon. In the present study, most species of Parasesarma are re-evaluated phylogenetically, using mitochondrial and nuclear molecular markers. The results show that the majority of the examined species cluster consistently with the type species Parasesarma plicatum . However, some species, among them the tree-climbing Parasesarma leptosoma, are clearly separated from this main clade of Parasesarma, forming a second stable monophyletic group, distinct from other known genera. Based on these results, and with additional support by morphological diagnoses highlighting consistent differences between the two species groups, we propose a new genus for the species clustering around P. leptosoma, proposing the new name Leptarma gen. nov.